2017
DOI: 10.21164/pomjlifesci.272
|View full text |Cite
|
Sign up to set email alerts
|

Osteosynthesis techniques used for mandibular sagittal split osteotomy – history of orthognathic procedures and modern practice

Abstract: Choosing an appropriate fixation technique after maxillary or mandibular osteotomy is one of the key factors affecting the success of orthognathic surgery. In line with the development of new surgical methods and techniques, the surgeons' approach to the fixation of bone fragments has evolved accordingly, varying from non-fusion to different osteosynthesis techniques. Advances in medical sciences and medical technologies, have changed our attitudes to bone fragment reduction in orthopaedics and traumatology, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Current research suggested that the theoretical basis for the rapid postoperative orthodontic tooth movement was the phenomenon of regional acceleratory phenomenon (RAP) (Amit et al, 2012; Mueller et al, 1991; Verna, 2016). Specifically, the orthognathic surgery‐mediated regional alveolar bone undergoing demineralization and remineralization, and triggered an active period of osteoclasts for 3–4 months (Li et al, 2018; Nowak & Trybek, 2016). However, there was still a lack of systematic research to illustrate the molecular mechanisms involved in osteoclastic activity induced by surgical trauma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current research suggested that the theoretical basis for the rapid postoperative orthodontic tooth movement was the phenomenon of regional acceleratory phenomenon (RAP) (Amit et al, 2012; Mueller et al, 1991; Verna, 2016). Specifically, the orthognathic surgery‐mediated regional alveolar bone undergoing demineralization and remineralization, and triggered an active period of osteoclasts for 3–4 months (Li et al, 2018; Nowak & Trybek, 2016). However, there was still a lack of systematic research to illustrate the molecular mechanisms involved in osteoclastic activity induced by surgical trauma.…”
Section: Introductionmentioning
confidence: 99%
“…surgery-mediated regional alveolar bone undergoing demineralization and remineralization, and triggered an active period of osteoclasts for 3-4 months (Li et al, 2018;Nowak & Trybek, 2016). However, there was still a lack of systematic research to illustrate the molecular mechanisms involved in osteoclastic activity induced by surgical trauma.…”
mentioning
confidence: 99%